System Modelling to Optimize the Number of Production of Men's Bags and Women's Bags to Obtain Maximum Profit in ABC Karawang Convection using Linear Programming - Wayan, Ni Wayan Puji Efpryani (Journal of Industrial Engineering and Halal Industries, 2025)
This study aims to optimize the production quantity of men's and women's bags to achieve maximum profit at ABC Karawang Convection. The company faces challenges in determining the ideal production quantity due to limited resources, resulting in unfulfilled market demand and suboptimal profit. The research method applied is Linear Programming using the Simplex approach, implemented through the CPLEX Solver software. The results indicate that the optimal solution is achieved by producing 1 unit of men’s bag and 82 units of women’s bags, yielding a maximum profit of IDR 3,740,000. This model provides an efficient production strategy and can serve as a decision-making foundation for production planning.